PARTICIPATION LEVEL OF INHABITANTS IN ECONOMICAL ACTIVITY (A Case Study on Program Penanggulangan Kemiskinan di Perkotaan in Kelurahan Pancoran Mas, Depok City) - Ade Andriyani; Tety Elida (Universitas Gunadarma, 2009)
This research is intended to measure participation of inhabitants in supporting Program Penanggulangan Kemiskinan di Perkotaan (P2KP). The research as well is intended to identify the unfulfill indicators as research instrument is questionnaire, which was distributed to 81 respondents. Respondents are them who received revolving fund from P2KP. Further, data was analyzed using statistics methods, namely descriptive statistics. Result shows that all indicators are scored above 60%, with mean value is 72.89%. It can be implied that inhabitants participation level in Kelurahan Pancoran Mas can be categorized as active.Key words : P2KP, inhabitants participation, revolving fund.